Early rehabilitation in the intensive care unit: An integrative literature review. Issue 4 (November 2015) - Sosnowski, Kellie; Lin, Frances; Mitchell, Marion L.; White, Hayden
Abstract: Objectives: The aim of this review is to appraise current research which examines the impact of early rehabilitation practices on functional outcomes and quality of life in adult intensive care unit (ICU) survivors. Review method used: A systematic literature search was undertaken; retrieved data was evaluated against a recognised evaluation tool; research findings were analysed and categorised into themes; and a synthesis of conclusions from each theme was presented as an integrated summation of the topic. Data sources: Electronic databases of PubMed, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Ovid Medline and Google Scholar were searched using key search terms 'ICU acquired weakness', 'early rehabilitation' 'early mobility' and 'functional outcomes' combined with 'intensive care' and 'critical illness'. Additional literature was sourced from reference lists of relevant original publications. Results: Five major themes related to the review objectives emerged from the analysis. These themes included: critically ill patients do not always receive physical therapy as a standard of care; ICU culture and resources determine early rehabilitation success; successful respiratory and physical rehabilitation interventions are tailored according to individual patient impairment; early exercise in the ICU prevents the neuromuscular complications of critical illness and improves functional status; early exercise in the ICU is effective, safe and feasible. Conclusions: A limited body of research supports early rehabilitation interventions to optimise the short term outcomes and long term quality of life for ICU survivors. Critical care nurses are in an excellent position to drive change within their departments ensuring that early rehabilitation practices are adopted and implemented.